Agro-tourism development sustainable analysis based on agricultural landscapes in Nagari Pandai Sikek, Tanah Datar District, West Sumatera - Jonni, Jonni; Nurhayati, Nurhayati; Sutjahyo, Surjono Hadi; Pravitasari, Andrea Emma; Rosadi, Rosadi (Brawijaya University, 2024)
In agro-tourism development, sustainable agricultural development in Nagari Pandai Sikek is expected to continue in terms of superior commodities and tourist attraction objects. This study aimed to analyze agro-tourism development based on agricultural and cultural landscapes in Nagari Pandai Sikek based on ecological, economic, socio-cultural, and institutional aspects, using Multi-Dimensional Scaling (MDS) analysis and the Rapfish method. The results of the status of agro-tourism development in Nagari Pandai Sikek on the Jorong Pagu-pagu of Nagari Pandai Sikek ecological dimension have the highest value of 56.76, with a fairly sustainable sustainability status. The economic dimension of Jorong Baruah of Nagari Pandai Sikek has the highest value of 84.41 with its sustainability status. The social dimension of Jorong Baruah of Nagari Pandai Sikek has the highest score of 99.98, with good sustainability status. The institutional dimension of Jorong Baruah of Nagari Pandai Sikek has the highest score of 99.98 with its sustainability status. The attributes that influence each dimension are the ecological dimension of land management and the economic dimension of harvest productivity. The dimension of community social organization is the institutional dimension of the tourism management group.